1993
DOI: 10.1016/0140-6736(93)90277-n
|View full text |Cite
|
Sign up to set email alerts
|

High serum procalcitonin concentrations in patients with sepsis and infection

Abstract: High concentrations of calcitonin-like immunoreactivity have been found in the blood of patients with various extrathyroid diseases. By means of a monoclonal immunoradiometric assay for calcitonin precursors, we have measured serum concentrations of procalcitonin in patients with various bacterial and viral infections. 79 children (newborn to age 12 years) in hospital with suspected infections were investigated prospectively. 19 patients with severe bacterial infections had very high serum concentrations of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
1,119
5
110

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,832 publications
(1,302 citation statements)
references
References 13 publications
35
1,119
5
110
Order By: Relevance
“…Small sample size and analytical restrictions of the assay constitute the main limitations of the present study. However, the immunoluminometric method for PCT measurement is widely accepted and was used to establish the role of PCT in sepsis [2]. Moreover, other parameters and clinical scoring systems examined in this study did correlate with outcome, regardless of the small number of cases.…”
Section: To the Editormentioning
confidence: 64%
See 2 more Smart Citations
“…Small sample size and analytical restrictions of the assay constitute the main limitations of the present study. However, the immunoluminometric method for PCT measurement is widely accepted and was used to establish the role of PCT in sepsis [2]. Moreover, other parameters and clinical scoring systems examined in this study did correlate with outcome, regardless of the small number of cases.…”
Section: To the Editormentioning
confidence: 64%
“…Serum procalcitonin (PCT)-a marker of septicemia and infection severity [2]-has also been proposed as an indicator of systemic inflammatory response in noninfectious situations [3,4]. As no data exist thus far on PCT in stroke, this study aimed to evaluate serum PCT changes in the acute stroke setting, and to correlate them with clinical and laboratory parameters and patient's outcome.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…trauma) [59]. -Procalcitonin has been proposed as a marker of infection [60][61][62][63]. Furthermore, it may be useful as an indicator of the severity of infection and as a guide for therapy (dose de-escalation [64]) in respiratory infections [61,62,[65][66][67][68].…”
Section: The Diagnosis Of Sepsismentioning
confidence: 99%
“…Levels above this value have been accepted to be pathological. [13][14][15][16] It has also been suggested that PCT levels may be increased in neonatal sepsis and its diagnostic utility is comparable that of with CRP. 12 As stated previously, clinical signs of neonatal sepsis are nonspecific and there is no sensitive and specific laboratory test for detecting an early-stage infection.…”
Section: Introductionmentioning
confidence: 99%